Nonlinear observer based control for travelling wave nuclear reactors based on the Lyapunov approach during load following operation. (October 2016) - Hassanvand, R.; Ansarifar, G.R.; Nasrabadi, M.N.
Highlights: A nonlinear observer based control has been developed for T.W.R nuclear reactors based on the six delayed neutron groups. The control system is guaranteed to be stable within a large range. The stability analysis has been given by means Lyapunov Approach. The comparison between S.M.C and the conventional PID controller shows a significant improvement in the power tracking. Abstract: Power control of the nuclear reactor is one of the most important subjects in each nuclear power plant. In this paper, a nonlinear controller using sliding mode method which is a robust nonlinear controller is designed to control a Traveling Wave Nuclear Reactor (TWR) power. The reactor core is simulated based on the point kinetics equations and six delayed neutron groups. Considering the limitations of the delayed neutron precursors densities measurement, a sliding mode observer is designed to estimate their values and finally a sliding mode control based on the sliding mode observer is presented to control the reactor core power. The stability analysis is given by means Lyapunov approach, thus the control system is guaranteed to be stable within a large range. Sliding Mode Control (SMC) is one of the robust and nonlinear methods which have several advantages such as robustness against matched external disturbances and parameter uncertainties. Since it has systematic design procedure, it is one of the most powerful solutions to design many practical control systems. The designed control system is evaluated in the presence of disturbances and uncertainties. The results show the robustness and performance of the used control system.